1989
DOI: 10.1002/1097-0142(19890401)63:7<1337::aid-cncr2820630719>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Detection of squamous cell carcinoma antigen in normal squamous epithelia and in squamous cell carcinomas of the uterine cervix

Abstract: Squamous cell carcinoma (SCC) antigen is a subfraction of tumor antigen TA-4 isolated from a cervical squamous cell carcinoma. The specificity of SCC antigen and the factors influencing its release into serum were evaluated. Antigen concentrations were measured in 157 tissue extracts and in 188 sera of patients with nonmalignant or malignant gynecologic diseases. A commercial radioimmunoassay based on polyclonal antibodies (Abbott Laboratories, North Chicago) was used. Cytosol concentrations were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 14 publications
(1 reference statement)
2
45
0
2
Order By: Relevance
“…This current study is consistent with the findings by Helmig et al (2002) where a significant reduction in M/NEI concentration in the amniotic fluid of asymptomatic women with preterm PROM, in the absence of chorioamnionitis, was observed. SCCA-1 is a broad inhibitor of cysteine proteinases, cathepsins L, S and K, which are implicated in ECM remodelling through elastin degradation (Schick et al 1998) and is localised in the squamous epithelial cells of the cervix and vagina (Crombach et al 1989, Cataltepe et al 2000. A decrease in SCCA-1 expression in the CVF of women with impending preterm PROM may reflect a concomitant increase in cathepsin activity occurring in the ECM of the supracervical membranes leading to their weakening and subsequent rupture.…”
Section: Discussionmentioning
confidence: 99%
“…This current study is consistent with the findings by Helmig et al (2002) where a significant reduction in M/NEI concentration in the amniotic fluid of asymptomatic women with preterm PROM, in the absence of chorioamnionitis, was observed. SCCA-1 is a broad inhibitor of cysteine proteinases, cathepsins L, S and K, which are implicated in ECM remodelling through elastin degradation (Schick et al 1998) and is localised in the squamous epithelial cells of the cervix and vagina (Crombach et al 1989, Cataltepe et al 2000. A decrease in SCCA-1 expression in the CVF of women with impending preterm PROM may reflect a concomitant increase in cathepsin activity occurring in the ECM of the supracervical membranes leading to their weakening and subsequent rupture.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ueda et al (1984) reported that the SCC antigen (referred to as TA-4) was detected in some adenocarcinomas of the uterine cervix and less frequently in those of the endometrium. Crombach et al (1989) showed elevated cytosolic SCC antigen protein in adenocarcinomas of the uterine cervix in comparison with other gynaecological adenocarcinomas. Takeshima et al (1992) detected mRNA of SCC antigen in the columnar cells of the cervix but not in the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…SCC is not organ specific (for cervix) or malignancy specific. Elevated concentrations have been found in patients with squamous cell carcinomas of the vulva, vagina, head and neck, esophagus, and lung (390,427,428 ), as well as in patients with benign diseases of the skin (e.g., psoriasis, eczema), lung (e.g., sarcoidosis), liver, and kidney.…”
Section: Scc Reference Intervalsmentioning
confidence: 99%